2021
DOI: 10.4187/respcare.08365
|View full text |Cite
|
Sign up to set email alerts
|

Telerehabilitation in Subjects With Respiratory Disease: A Scoping Review

Abstract: Considering the current coronavirus disease (COVID-19) pandemic, telerehabilitation may be a viable first-line option for patients with respiratory tract disease. To date, there has been no systematic review on telerehabilitation for respiratory tract diseases, including COVID-19. Therefore, this scoping review aimed to determine what telerehabilitation for patients with respiratory tract diseases consists of, how safe telerehabilitation is for patients with respiratory tract diseases, and how feasible telereh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 46 publications
2
20
1
1
Order By: Relevance
“…Conversely, the facilitators for telerehabilitation include less travel time for patients, ease of use of the system and a shorter waiting period for patients [48]. Taito et al [49] in their paper on telerehabilitation in patients with respiratory disease during the pandemic, described how the reported number of adverse events was low and the average treatment compliance rate was greater than 70%. In the Netherlands, Bos et al [48] showed positive results after using telemedicine for patients with rheumatic and musculoskeletal diseases during the COVID-19 pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, the facilitators for telerehabilitation include less travel time for patients, ease of use of the system and a shorter waiting period for patients [48]. Taito et al [49] in their paper on telerehabilitation in patients with respiratory disease during the pandemic, described how the reported number of adverse events was low and the average treatment compliance rate was greater than 70%. In the Netherlands, Bos et al [48] showed positive results after using telemedicine for patients with rheumatic and musculoskeletal diseases during the COVID-19 pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…However, in general, positive results are demonstrated in emergency room admissions, exacerbation-related readmissions, early detection of acute exacerbation of COPD, and health-related outcomes [25][26][27][28][29][30][31][32][33][34][35][36]. Additionally, a review of tele-rehabilitation papers showed similar, favorable outcomes compared to standard, center-based pulmonary rehabilitation in functional exercise capacity, health related quality of life, and dyspnea [37][38][39][40][41]. Both interventions were safe and tele-rehabilitation patients were more likely to complete the program.…”
Section: Published Results On Effectivenessmentioning
confidence: 99%
“…Exercise capacity (6 min walk test), St George's Respiratory Questionnaire (SGRQ), breathlessness on the Chronic Respiratory Questionnaire (CRQ) dyspnea domain score [38] Cardiopulmonary diseases Exercise capacity (6 min walk test), peak oxygen consumption, quality of life [39] Respiratory diseases Safety Feasibility Reduced face-to-face rehabilitation therapy [38,40] Respiratory diseases Assessment of sit-to-stand tests, Timed Up and Go step test, 6 min walk test (not for patients at risk of desaturation)…”
Section: Copdmentioning
confidence: 99%
“…34 Taito et al in a scoping review also included people recovering from COVID-19. 35 A recently published Cochrane review assessed the effectiveness and safety of telerehabilitation for people with CRDs when compared with Centre-PR or no rehabilitation 36 and concluded that primary or maintenance PR telerehabilitation achieved similar outcomes to Centre-PR. In this review, remote delivery of PR was defined by the use of telecommunications technology to deliver PR services to individuals or groups (either physical or virtual) in any location, including in the patient's home or at a healthcare centre.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…In contrast, in our review, the definition of Home-PR is that the sessions are undertaken by an individual by themselves (though a family member may be involved) and typically at home. Apart from baseline and post-PR assessments, 35 the patient does not attend a centre (either a hospital centre or a local ‘satellite’ centre) and is not supervised face-to-face by a healthcare professional (though there may be remote communication from a healthcare professional for some or all of the session).…”
Section: Introductionmentioning
confidence: 99%